Power Analysis in Penta Helix Practices in The Citarum Harum Programme (Open Society Conference, 2023)
The Citarum has gone through various programmes from time to time. The first Citarum management program was launched in 1989 under the name of Kali Bersih Program (Prokasih) until Presidential Regulation No. 15/2018 on the Acceleration of Citarum River Watershed Pollution and Damage Control (PPK DAS) which was realised through the Citarum Harum Program. Currently, Citarum Harum is managed under the Pentahelix Concept Scheme that involves five main sectors, including academia, business, community, government, and media as actors who will collaborate in creating a holistic solution to the problem of Citarum River degradation. This research seeks to analyse the power relations formed from the interactions resulting from the implementation of Penta helix practices in the Citarum Harum programme. The aim is to see whether power is evenly dispersed across all Penta helix stakeholders or whether there is dominance and inequality of power relations in the Penta helix practice that has an impact on the optimisation of the Penta helix model in the Citarum Harum programme. This study uses a qualitative method by conducting interviews with the Penta helix pillars and is supported by documents on the implementation of the Citarum Harum programme. The results show that there is an imbalance of power relations between the pillars of the Penta helix. This occurs because the Penta helix is promoted as a concept that does not have a clear operationalisation of the roles and functions of each pillar. Therefore, the government as the leading sector once again dominates the process of program collaboration that has an impact on optimising the handling of the Citarum River.